Association Of Anthropometric Measurement, Uric Acid, Vitamin D, Albumin, And Diabetes Mellitus With Frailty In The Elderly A Study At Bina Bhakti Elderly Home - Santoso, Alexander Halim; Martin, Alfianto; Jap, Ayleen Nathalie; Lumintang, Valentino Gilbert; Alvianto, Fidelia (Pusat riset dan Inovasi Nasional, 2025)
Frailty is a common syndrome in older adults, marked by declining physiological reserves and increased vulnerability to adverse health outcomes. It impacts quality of life and links to higher morbidity, mortality, and healthcare needs. Identifying frailty markers early helps prevent or delay its onset. In Indonesia, frailty affects 10–20% of the elderly, with higher rates in rural areas and those over 75, driven by poor nutrition, chronic diseases, and limited healthcare access. This study explores these factors and their relationship with frailty in elderly residents of Bina Bhakti Elderly Home. This cross-sectional study analyzed anthropometric measurement, uric acid, vitamin D, albumin, and diabetes mellitus with frailty in 42 elderly residents, excluding those with cognitive impairments, acute illnesses, or psychiatric disorders. The analysis identified fasting blood glucose, HbA1c, and albumin as significant predictors of frailty, highlighting the importance of glucose regulation and nutritional status in frailty risk among the studied population. Fasting blood glucose, HbA1c, and albumin emerged as key predictors of frailty, highlighting the roles of glycemic control and nutritional health in reducing frailty risk. Lower fasting blood glucose and higher albumin levels were protective, while higher HbA1c increased vulnerability. Targeted interventions in these areas may effectively mitigate frailty risk.